“SU JOK” THERAPY AND SCLEROLOGY PROFILE MONITORING FOR MANAGING CHEST PAIN AT HOME WHILE AVOIDING HOSPITAL ADMISSION DURING THE COVID-19 PANDEMIC: A CASE STUDY - Intansari Nurjannah (Belitung Raya Foundation, Indonesia, 2020)
Background: The COVID-19 pandemic has resulted in people avoiding hospital admission for non-COVID patients and forcing people to seek help via telehealth or alternative medicine. Case study: A 30-year-old man from Solo, Indonesia, complained of left chest discomfort with an irregular heartbeat. This man sent an inquiry and his left eye sclera profile through WhatsApp on July 20, 2020 to a researcher, who is a nurse and “Su jok” therapist. Protocol for “Su jok” therapy was sent back through WhatsApp, and after applying the treatment for 30 minutes, the patient felt better, and symptoms were less severe. The full protocol to be applied for the following days was then sent to the patient. After three weeks, there was a less sharp red line in the sclera area of the vessel blockage, and he only experienced mild symptoms. Conclusion: The case study shows that “Su jok” therapy may become an alternative therapy for managing chest pain at home. Sclerology can be a complementary choice to monitor a patient’s heart condition. Visiting the hospital, however, is still necessary when the symptoms become worse.